Assessment of Coilia mystus and C. nasus in the Yangtze River Estuary, China, Using a Length-Based Approach - Lu Zhai; Zengguang Li; Yongbin Hu; Chengwei Huang; Siquan Tian; Rong Wan; Daniel Pauly (Fishes, 2022)
An assessment of the stock status and historical changes in abundance of Coilia mystus and C. nasus in the Yangtze River Estuary, China, was carried out based on field surveys conducted in 2019–2020 and published length-frequency (L/F) data from earlier periods. These two species’ current and past relative biomasses (B/BMSY) were estimated using a length-based Bayesian biomass estimation method (LBB). The LLB method also estimated their asymptotic lengths (Linf), current and optimum mean lengths at first capture (Lc; Lopt_c), and their ratios of natural and fishing mortality to growth (M/K; F/K). In response to increasing fishing pressure, both species’ maximum lengths declined, along with their B/BMSY ratio, which declined for C. mystus from 1.7 in 1982 to 0.47 in 2020 and for C. nasus from 1.7 in 2006 (or earlier) to 0.17 in 2020. These assessments show that both of the two Coilia species are overfished, with C. nasus impacted more severely than C. mystus. The prospect for the recovery of these two species is briefly discussed. This contribution will help toward the management of the population of these two Coilia species and provides a basis for evaluating the effect of the 10-year fishing ban in the Yangtze River.